Validation of plantar pressure simulations using finite and discrete element modelling in healthy and diabetic subjects. Issue 13 (3rd October 2017) - Aerts, W.; Scarton, A.; De Groote, F.; Guiotto, A.; Sawacha, Z.; Cobelli, C.; Vander Sloten, J.; Jonkers, I.
Abstract: Plantar pressure simulation driven by integrated 3D motion capture data, using both a finite element and a discrete element model, is compared for ten healthy and ten diabetic neuropathic subjects. The simulated peak pressure deviated on average between 16.7 and 34.2% from the measured peak pressure. The error in the position of the peak pressure was on average smaller than 4.2 cm. No method was more accurate than the other although statistical differences were found between them. Both techniques are thus complementary and useful tools to better understand the alteration of diabetic foot biomechanics during gait.